Inflammatory bowel disease in South-Eastern Norway III (IBSEN III): a new population-based inception cohort study from South-Eastern Norway. (3rd August 2021) - Kristensen, Vendel A.; Opheim, Randi; Perminow, Gøri; Huppertz-Hauss, Gert; Detlie, Trond Espen; Lund, Charlotte; Andersen, Svend; Olsen, Bjørn C.; Johansen, Ingunn; Medhus, Asle W.; Vatn, Simen; Brackmann, Stephan; et al.
Abstract: Background and aim: Modern treatment strategies for inflammatory bowel disease (IBD) are postulated to change the natural disease course. Inception cohort studies are the gold standard for investigating such changes. We have initiated a new population-based inception cohort study; Inflammatory bowel disease in South Eastern Norway III (IBSEN III). In this article, we describe the study protocol and baseline characteristics of the cohort. Methods: IBSEN III is an ongoing, population-based observational inception cohort study with prospective follow-up. Adult and pediatric patients with suspected IBD in the South-Eastern Health Region of Norway (catchment area of 2.95 million inhabitants in 2017), during the 3-year period from 2017 to 2019, were eligible for inclusion. Comprehensive clinical, biochemical, endoscopic, demographic, and patient-reported data were collected at the time of diagnosis and throughout standardized follow-up. For a portion of the patients, extensive biological material was biobanked. Results: The study included 2168 patients, of whom 1779 were diagnosed with IBD (Crohn's disease: 626, ulcerative colitis: 1082, IBD unclassified: 71). In 124 patients, there were subtle findings indicative of, but not diagnostic for, IBD. The remaining 265 patients were classified as symptomatic non-IBD controls. Conclusion: We have included patients in a comprehensive population-based IBD cohort from a catchment population of 2.95 million, and a unique biobank with materials from newly diagnosed and treatment-naïve IBD patients and symptomatic non-IBD controls. We believe this cohort will add important knowledge about IBD in the years to come.